Spa towns in Germany: Preferred moving locations for older people? - Diller, Christian; Litmeyer, Marie-Louise; Göbel, Jonas (ERDKUNDE, 2023)
From the available studies on the spatial patterns and causes of migration of older people, it can be assumed that the ‘wellness’ infrastructure is an important pull factor of places. In the absence of differentiated data on this infrastructure at the municipal level, this paper uses the variable ‘spa’ as a placeholder for this wellness infrastructure. It is assumed that health resorts offer special qualities of this infrastructure. This is reflected in a particularly positive population development of these places. However, the area-wide and at the same time spatially small-scale consideration of the population in two age groups over 50 years could not confirm this assumption. Only in some types of spa towns, such as the Baltic resorts, was the development in these age groups clearly above average. In some places, such as the North Sea islands and spa towns in the alpine upland and low mountains, there were even declines. The spa town status by itself is not sufficient to explain the attractive-ness of these places for higher age groups. This requires further analyses, especially of the infra-structure facilities, local recreational qualities, housing availability and the subjective motivations of the incoming people.